Uma análise crítica sobre a reconstrução da trajetória histórica da Sociologia na educação básica: investigando o chamado período de exclusão1 - Alexandre Barbosa Fraga (Ciências Sociais Unisinos)
Among the many ways in which the historical trajectory of Sociology as a discipline of basic education in Brazil can be reconstructed, one ofthem is through educational reforms and changes in legislation, marking four great periods: institutionalization (1890-1941), exclusion (1942-1981), gradual reinsertion (1982-2007) and obligatory return (2008-2017). However, despite its importance, there is in the scientific literature a critique of the re-construction of the trajectory of this discipline by legal landmarks: that it is limited and superficial. In response to this, more recent research has sought to analyze this trajectory in a more complex way. However, even they did not study the second halfof the 1940s and the 1950s, 1960s and 1970s, because unrestricted adherence to legal landmarks led to the failure to seek sociology in basic education between 1942 and 1981, with the exception of the normal course. Thus, the objective of this article is to prove the existence ofSociology teaching in the considered period of exclusion. For this, will be investigated a course produced by the TV Cultura of São Paulo and transmitted between 1969 and 1970. In these classes by television, Sociology was actively pres-ent in the section "Human Sciences", which was prepared with the participation of USP professors. Therefore, the research results point to the potentiality ofseeking Sociology in the so-called exclusion period, provided a broader view of curriculum, beyond legal landmarks and disciplinary curriculum. This means mobilizing, therefore, different agents and fields involved in the recontextualization ofknowledge, as theorized by the sociologist Basil Bernstein.